Larval collectors network documents the spread of the invasive bivalve Pinctada radiata in the Mediterranean Sea - Júlia García-Colomé; Iris E. Hendriks; Isabel Abel-Abellán; Giorgio Aglieri; Peru Agueda; Natalia Aisa-Bravo; Elvira Álvarez; María P. Andrada-Nicolás; Irene Antón-Linares; Elisa Arroyo-Martínez; Carolina Audisio-Pacheco; Tatjana Bakran-Petricioli; et al. (Marine Environmental Research, 2026)

Fan Mussel (Pinna nobilis L.) Spat Collection, Monitoring of Early Growth and Conservation Implications by Deploying Conventional Aquaculture Methodology - John A. Theodorou; Efthimios Spinos; Alexis Ramfos; Ioannis E. Tsamadias; Vlasoula Bekiari; Maria Kamilari; Maria-Myrto Ntouni; Dimitrios Tsotsios; Konstantinos Feidantsis; Athanasios Lattos; Ioannis A. Giantsis; Basile Michaelidis (Journal of Marine Science and Engineering, 2024)
Pinna nobilis, endemic to the Mediterranean Sea, has been experiencing a gradual population decline over recent decades due to anthropogenic pressures on its ecosystems. However, since 2016, its populations have suffered significant reductions because of pathological issues affecting the species across all its habitats. Aquaculture techniques to support the limited natural recruitment P. nobilis efforts is examined. Artificial substrates for larval attachments in aquaculture infrastructures promote the survival of the juveniles that is further enhanced through protected pre-growing “nursery” farming conditions. Specific spat collectors were placed in 2 cage-fish farms in SW Amvrakikos Gulf. The harvested spats from were transferred to pre-grow in trays hanged on a long line farm mussel that is acting as a protected “nursery”, avoiding predation and any human accidentally disturbance. The survival and growth of 12 juveniles P. nobilis spat (shell length 38.1 ± 9.2 mm) in captivity (31 October 2023–15 March2023) was investigated. Out of the 12 individuals collected, 3 were examined for the presence of pathogens; only 7 survived, exhibiting enhanced growth (shell length 54.3 ± 11.6 mm) after 134 days in the nursery. The results highlight the significant role of aquaculture techniques in efforts to conserve a threatened species as well as the need for the creation of a protocol to ensure the conservation of P. nobilis.

Ecological and environmental characteristics of a seagrass-dominated hypersaline coastal Mediterranean lagoon: a multidisciplinary approach - A. Ramfos; A. Alysandratou; O. Katsani; S. Faulwetter; K. Nikolakopoulos; P. Avramidis (Aquatic Sciences, 2024)
In the present paper, sedimentological, water physicochemical data and biological benthic assemblages are compiled to provide an integrated environmental assessment of a protected shallow Mediterranean lagoon with a long history of management interventions (Klisova Lagoon, Western Greece). Satellite remote sensing techniques were used for mapping the seagrass Cymodocea nodosa (Ucria) Asch, which presents an extensive expansion in the study area. The results showed that Klisova is a hypersaline, well-oxygenated lagoon presenting changes in temperature, salinity, pH and dissolved oxygen over the course of 1 year, but largely lacks any spatial differentiation other than an east–west gradient in salinity in spring and summer. Sediment was classified as silty sand to silt, rich in total organic carbon (TOC), total nitrogen (TN) and total phosphorus (TP). The benthic community was characterised by a high species richness and the presence of marine species, without a clear spatial pattern. The multivariate-AZTI’s marine biotic index (M-AMBI) showed that the ecological quality of the macrobenthos was good in most stations. C. nodosa covered over 70% of the lagoon area and formed meadows even in the eastern part of the lagoon where salinity during spring and summer was close to the reported upper tolerance limit of the species (> 50). The present multidisciplinary approach provides valuable baseline information on various components of the ecosystem which can be used as a basis for management bodies and future conservation plans for the lagoon.

Status, distribution, and threats of the last surviving fan mussel populations in Greece - ORESTIS PAPADAKIS; IOANNIS MAMOUTOS; ALEXIS RAMFOS; GAETANO CATANESE; EVANGELOS PAPADIMITRIOU; JOHN THEODOROU A.; COSTAS BATARGIAS; CHARIKLEIA PAPAIOANNOU; MARIA KAMILARI; ELINA TRAGOU; VASSILIS ZERVAKIS; STELIOS KATSANEVAKIS (Mediterranean Marine Science, 2023)
Since the first confirmed records of mass mortality events (MME) in the Aegean Sea in 2018, Pinna nobilis populations in Greek seas have been decimated. To bolster recovery efforts, this study aimed to assess the status of fan mussel populations in the Aegean and Ionian seas and investigate potential recolonization through natural recruitment. From May 2022 to May 2023, 163 independent underwater visual surveys were conducted across various locations and depths along the Greek coastline. A total of 4348 P. nobilis individuals was recorded, of which 87.3% were found dead and 12.7% were alive. The sole surviving fan mussel populations were located in the semi-enclosed gulfs of Amvrakikos in the Ionian Sea and of Kalloni in the Aegean Sea, with estimated recent mortality rates (excluding potential poaching) of 7.7% and 6.3%, respectively. To track potential new recruitment, a network of larvae collectors was deployed in multiple locations. Additionally, an ocean circulation model (OCM) was developed to predict the export and fate of larvae from the surviving populations in the Marmara Sea towards the Aegean Sea. Beyond the MME, this study identified several other threats, which significantly endanger fan mussel survival. The findings of this study underscore the urgent need to implement protection measures and restoration actions to enhance the chances of P. nobilis survival and recovery in the Greek seas.

Pinna nobilis in the Greek seas (NE Mediterranean): on the brink of extinction? - MARIA ZOTOU; PAVLOS GKRANTOUNIS; ELPIDA KARADIMOU; KONSTANTINOS TSIRINTANIS; MARIA SINI; DIMITRIS POURSANIDIS; MARTA AZZOLIN; THANOS DAILIANIS; ELENI KYTINOU; YIANNIS ISSARIS; VASILIS GERAKARIS; MARIA SALOMIDI; et al. (Mediterranean Marine Science, 2020)
The Mediterranean endemic fan mussel Pinna nobilis is suffering an ongoing basin-scale mass mortality event (MME) since 2016. As most Mediterranean populations have collapsed, the species has been declared as Critically Endangered in the IUCN Red List of threatened species. In an effort to track the progress of the MME and provide updated information on the status of the species in the Greek seas, we compiled data collected through dedicated surveys and opportunistic assessments during 2019 and 2020. A total of 14589 fan mussel individuals, of which 81.1% dead, were recorded in 258 site surveys. Of the remaining 2762 live individuals, 256 were juveniles. Two marine areas which still sustain living populations were identified, namely Kalloni Gulf (Lesvos Island), and Laganas Bay (Zakynthos Island). The inner part of Kalloni Gulf appears to maintain the largest surviving population of the species in the eastern Mediterranean, with an abundance estimate of 684000 individuals (95% confidence interval: 322000-1453000). Solitary, potentially resistant, scattered individuals were recorded in several sites. Other previously abundant populations that had been assessed in the past, specifically those of Lake Vouliagmeni (Korinthiakos Gulf), Souda Bay (Crete) and Gera Gulf (Lesvos Island), and which collectively summed up to ~350,000 individuals, have now been wiped out. Our results document the collapse of most P. nobilis populations throughout the Greek seas. The MME has substantially progressed between early 2019 and mid-2020, as indicated by the increase of mortality at sites consecutively monitored multiple times. This work highlights the urgent need for continuous monitoring of surviving populations and calls for the immediate implementation of an effective protection and management strategy that will ensure the persistence of surviving individuals and the production of resistant offspring.

Sex‐specific daily spawning seaward migration of striped mullet Mugil cephalus in a coastal lagoon - G. Katselis; K. Koukou; A. Ramfos; D. K. Moutopoulos (Journal of Fish Biology, 2015)
The sex‐specific daily spawning seaward migration of striped mullet Mugil cephalus was analysed in Palaiopotamos Lagoon (western Greek coast, eastern Mediterranean Sea) in an 86 day time series. The data set included the daily number of M. cephalus catches in barrier traps, as well as a time series of some weather variables. The analysis revealed an important linkage of the daily migration rate as well as a sex‐specific response of the species to the lunar cycle and the short‐term fluctuation of weather variables. The daily migration pattern of females was more persistent than that of males, indicating a possible female leadership role during the spawning migration. Multiregression models described quite accurately the sex‐specific daily migration rates of the species, thus providing a potentially powerful tool regarding the lagoon fishery management of M. cephalus , especially in the context of climate change.

Zooplankton diversity and distribution in a deep and anoxic Mediterranean coastal lake - G. KEHAYIAS; A. RAMFOS; S. IOANNOU; P. BISOUKI; E. KYRTZOGLOU; A. GIANNI; I. ZACHARIAS (Mediterranean Marine Science, 2013)
The variation of the smaller size fraction of zooplankton was investigated during a two-year period in a brackish deep and anoxic coastal lake of western Greece (Aitoliko), along with the specific environmental characteristics of this ecosystem. The zooplanktonic community comprised a relatively small number of taxa and it was dominated by brackish-water calanoid copepods (Paracartia latisetosa, Calanipeda aquaedulcis) and in certain periods by rotifers and tintinnids. The zooplankton abundance showed an increase in the warmer period starting from late spring and reached maximum values in July. In the well oxygenated surface layer, temperature was the most important parameter influencing the seasonal cycles of all groups. In contrast, the oxygen depletion a few meters under the surface affected the vertical distribution of most of the zooplankton groups, which were found restricted in the surface layer especially from spring until autumn. Only the meroplanktonic larvae of polychaetes presented increased proportions in the deeper layers. Salinity has not significantly influenced the zooplanktonic assemblages. The results point out the degraded status of the Aitoliko basin where the hypoxic/anoxic layers resulted to a high portion of dead organic material identified as copepod carcasses, and underlines the necessity of monitoring of this ecosystem.

Zooplankton diversity and distribution in a deep and anoxic Mediterranean coastal lake - G. KEHAYIAS; A. RAMFOS; S. IOANNOU; P. BISOUKI; E. KYRTZOGLOU; A. GIANNI; I. ZACHARIAS (Mediterranean Marine Science, 2013)

Differential patterns of mesozooplankters’ distribution in relation to physical and biological variables of the northeastern Aegean Sea (eastern Mediterranean) - S. Isari; S. Psarra; P. Pitta; P. Mara; M. O. Tomprou; A. Ramfos; S. Somarakis; A. Tselepides; C. Koutsikopoulos; N. Fragopoulu (Marine Biology, 2007)